Linkage Program Bank Syariah Dengan BMT: Tinjauan Kritis Bagi Pengembangan Sistem Keuangan Islam Yang Lebih Kaffah - Nafik HR, Muhammad (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This study aims to determine the BMTâs reason for not continuing linkage with Islamic Bank.Â Whereas linkage program is a good strategy to achieve a more inclusive financial system.Â This study used a qualitative approach and single-case studies as the strategy. Primary dataÂ collection using in-depth interview, while secondary data obtained from the annual financialÂ statements of BMT. The expalanation building was used as the technique of analysis byÂ explaining the results of in-depth interviews, in order to know what is BMTâs reason for this case.The results showed that the linkage program that used mudaraba contract which the rateÂ of return should be variable on the income of BMT, but in fact is still based on the amount ofÂ financing. Linkage contract which is not in accordance with mudaraba system contractÂ caused BMT did not continue linkage with Islamic banks.